First approaches to jurisdictional decision-making bodies of the Peruvian Judiciary - Godenzi Cuéllar, Ricardo (2022)
In this article we show the initial findings on the different types of courts existing in the Peruvian Judiciary today, their primary characteristics and what the creation of a complex diversity of categories of courts can reveal in terms of response of the Peruvian State against the social conflicts it is obliged to address.